The Efficiency of Satellite Automatic Identification System (Sat-AIS) Device for Monitoring Small Scale Fisheries in Ghana - Agyei, Daniel (Fishery Technology, 2023)
This study employed Satellite Automatic Identification System (Sat-AIS) to monitor the activities of artisanal tuna fishing canoes in Ghana. Class-B transponders were mounted on two wooden canoes operating from Albert Bosomtwe Sam fishing harbour and their activities monitored over a period of six months. The canoes were mainly involved in the harvesting of tuna off the coast of Ghana. The results indicated that skipjack (Katsuwonus pelamis), bigeye tuna (Thunnus obesus), yellowfin tuna (Thunnus albacares) and frigate tuna (Auxis thazard) dominated the species landed during the study period. Based on the analysis of the speed profiles from the canoe trajectories obtained from AIS data, speeds between 2 knots to 4.3 knots was classified as fishing speeds for canoe fisheries. Findings from this study suggest that Sat-AIS, augmented by a Class-B transponder could be a useful tool in fisheries management for the small scale fishing fleet in Ghana. Based on the findings of this study, it is recommended that the Central government should legalise and make it mandatory for all small scale fishing fleets to have the device to enhance surveillance, monitoring and control of small scale fisheries in Ghana.